2015
DOI: 10.1021/acs.analchem.5b03432
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quantification Using Controlled DNA Melting Transitions in Bivalent Probe Assemblies

Abstract: Homogenous protein assays, despite the potential for mix-and-read workflows, have eluded widespread acceptance due to interferences in biological matrices and limited multiplexability. Here, we employ standard qPCR instrumentation for thermofluorimetric analysis of bivalent probe (TFAB) assemblies, allowing protein levels to be quantitatively translated into multiplexable DNA melting transitions within 30 min. As protein-bound bivalent probes are thermodynamically more stable than unbound probes, differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(80 citation statements)
references
References 13 publications
4
76
0
Order By: Relevance
“…We have previously shown that this approach allows separation of signal and background (two peaks for each trace in Figure 1B) and effectively negates matrix-based interferences. 10,13 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that this approach allows separation of signal and background (two peaks for each trace in Figure 1B) and effectively negates matrix-based interferences. 10,13 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the quality of this separation was comparable to our prior results using thrombin aptamer pairs yet was significantly improved compared to our in-house synthesized antibody-oligos. 10 This enhancement could be a result of either the improved purification of the probes or the simplification of the proximity assembly in this version of the assay, which does not require connector oligos. Leveraging the blank (zero insulin) subtraction method approach presented in our prior work, 13 the insulin-dependent portions of the TFA curves could then be easily visualized (Figure 2B) and applied for the quantitative analysis presented below.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations